Shameless. The eleventh and final season [videorecording (DVD)]. - Macy, William H., 1950-; White, Jeremy Allen; Cutkosky, Ethan, 1999-; Hampton, Shanola (Warner Bros. Home Entertainment, 2021)
As Frank confronts his own mortality, Lip struggles with becoming the family patriarch. Newlyweds Ian and Mickey figure out their committed relationship, while Deb embraces single motherhood. Lastly, Cart finds an unlikely new career in law enforcement while Kevin and V fight for their life on the South Side.